2023
DOI: 10.1590/1980-220x-reeusp-2023-0191en
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acupuncture and auriculotherapy in the control of chemotherapy-induced nausea and vomiting: a Pilot Study

Sabrina Ferreira Monteiro Morais,
Ruth Natalia Teresa Turrini

Abstract: Objective: To evaluate the effectiveness of acupuncture and auriculotherapy protocol in relieving chemotherapy-induced nausea and vomiting in cancer patients compared to the antiemetic protocol. Method: Pilot study of a pragmatic two-arm clinical trial: an acupuncture group received systemic acupuncture, auriculotherapy, and antiemetic protocol; a control group used antiemetic protocol. The sample consisted of 42 patients with cancer of the gastrointestinal system or multiple myeloma. The outcome was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Acupuncture has demonstrated efficacy in treating a range of conditions, including gastrointestinal (GI) diseases [1], cardiovascular diseases [2], chronic pain [3], chemotherapyinduced emesis [4], inflammation [5], and others. Previous studies demonstrated anatomical/physiological evidence of how acupuncture works.…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture has demonstrated efficacy in treating a range of conditions, including gastrointestinal (GI) diseases [1], cardiovascular diseases [2], chronic pain [3], chemotherapyinduced emesis [4], inflammation [5], and others. Previous studies demonstrated anatomical/physiological evidence of how acupuncture works.…”
Section: Introductionmentioning
confidence: 99%